Perception of learning communication using google meet in Malikussaleh University environment - Lala Syafira Ramadhani; Cindenia Puspasari; Muhammad Ali; Mursalin Mursalin (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
The purpose of this study is to analyse how learning communication is carried out at Malikussaleh University using google meet which is carried out during online learning. This research uses qualitative methods. The data collection methods used are interviews, observation and documentation. Data sources come from primary data and secondary data. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of this study are that learning communication using google meet is considered less effective in learning and has advantages and disadvantages when used during learning. using google meet has disadvantages such as requiring a stable signal, using a lot of quota, and consuming a large mobile phone memory capacity because lecture material is sent via email or whatsap, then a little difficult to be interactive and an inadequate learning environment causes unfocused learning and sore eyes and fatigue due to staring at the screen for a long time and many students become passive.